Pengaruh Profitabilitas, Kebijakan Hutang, Likuiditas dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Agustina Putri Kurnia Sari; Nurma Gupita Dewi (Accounting Global Journal, 2023)
AbstractThe aim of this research is to ascertain how firm value is affected by profitability, debt policy, liquidity and firm size. For the 2019-2021 period, this research collected 18 samples of food and beverage companies registered on the IDX using a purposive sampling technique. The analysis technique used is multiple linear using SPSS version 20. The results of this research show that profitability has a positive and significant effect on firm value, debt policy and liquidity have a negative and insignificant effect on firm value. Meanwhile, firm size has a positive and insignificant effect on firm value.